Cysteamine as a Future Intervention in Cystic Fibrosis Against Current and Emerging Pathogens: A Patient-based ex vivo Study Confirming its Antimicrobial and Mucoactive Potential in Sputum - Devereux, Graham (EBioMedicine, 2015)
BACKGROUND: Cysteamine has recently been shown to have in vitro properties potentially therapeutically beneficial in cystic fibrosis (CF). In this study we investigated the antimicrobial and mucolytic activity of cysteamine against the complex biologic matrix of CF sputum. METHODS: Sputum samples were obtained from 23 CF adults. Sputum polymicrobial content after in vitro exposure to cysteamine and standard CF antibiotics was assessed after a single exposure and after 14 days low-dose exposure. The effect of cysteamine on sputum spinnbarkeit was assessed. FINDINGS: Cysteamine reduced sputum polymicrobial burden by 3 · 18 (95% CI 2 · 30–4 · 07, p < 0.001) log(10) units after 24 h incubation. Combined cysteamine and tobramycin reduced polymicrobial burden by a further 3 · 75 (95% CI 2 · 63–5 · 07, p < 0 · 001) log(10) units above that seen with tobramycin. Repeated low dosing with cysteamine reduced sputum polymicrobial load from day 10 onwards (p = 0.032). Cysteamine reduced CF sputum viscoelasticity, sputum spinnbarkeit cysteamine 11.1 mm/s (95% CI 3.95–18.2) vs DNAse 1.69 mm/s (95% CI 0.73–2.65), p = 0.016. Cysteamine was active against Mycobacterium abscessus as a monotherapy and also potentiated the effects of amikacin and azithromycin. CONCLUSION: Further investigation is required into the therapeutic potential of cysteamine in CF to treat emerging as well as established microbial pathogens and as a mucolytic agent.